PESQUISA NA GRADUAÇÃO DE ADMINISTRAÇÃO: MEDIAÇÃO NECESSÁRIA AO PROCESSO ENSINO- APRENDIZAGEM - Mônica Mota Tassigny; Marcus Vinicius de Oliveira Brasil (Revista Gestão Universitária na América Latina, 2012)
The research is a legitimate process of knowledge construction and the classroom can and should be an area for such construction. This article, which is the result of a bibliographic review and a documental research, also considering the practical experience in teaching in higher education, aims to discuss the importance of research in a management undergraduate course. In this sense, science is conceptualized as a particular field of human knowledge; research, as an instrument to produce it and, especially linked with formative practice, therefore, electing the research and its possibilities as the foundation of the teaching-learning of management students, with the aim to awaken in students a taste for knowledge, motivation to learn and, above all, passion for research, as noted by Cecilia Minayo (1994), who conceptualizes this process as a harmonious blend of theory, method and creativity to produce knowledge and ensures continued dynamics in the task of trying to understand the reality and unravel its mysteries. In this perspective, we seek to take advantage of numerous possibilities that offer the classroom as a meeting place, exhibition of doubt, the clash of ideas and to build relationships. Thus, this article presents some clips or fragments of these experiences with research.